Influence of intra-oral sensory impairment by anaesthesia on food comminution and mixing in dentate subjects - Yoshida, E.; Fueki, K.; Wakabayashi, N. (Journal of oral rehabilitation, 2015)
Summary Sensory input from sensory receptors regarding food morsels can affect jaw motor behaviours during mastication. The aim was to clarify the effects of intra‐oral sensory input on the food‐comminuting and food‐mixing capacities of dentate subjects. Eleven dentate subjects without sensory dysfunction in their oro‐facial region participated in this study. Local anaesthesia was achieved on the periodontal structures and on the oral mucosa of the subjects' preferred chewing side by injecting a lidocaine solution with adrenalin. At baseline (control) and after anaesthesia, data on the subjects' food‐comminuting and food‐mixing capacities were gathered. The food‐comminuting capacity was quantified by measuring the degree of pulverisation of peanuts (objective hardness; 45·3 [Newton, N]) after a prescribed 20 chewing strokes. The food‐mixing capacity was measured as the degree of immixture of a two‐coloured paraffin wax cube after 10 chewing strokes. Wax cubes of three different hardness levels were used (soft, medium and hard: 20·3, 32·6 and 75·5 [N], respectively) and were chewed in random order. After anaesthesia, the subjects' food‐comminuting capacity significantly decreased (P < 0·001), as did the food‐mixing capacity for each hardness level of the wax cubes (P < 0·01). A significant correlation was observed between the objective hardness values and the anaesthesia effects for the food‐mixing capacity (P < 0·05), indicating that after anaesthesia, deterioration of the mixing capacity increased as the hardness increased. In conclusion, intra‐oral sensory input can affect both food‐comminuting and food‐mixing capacities.